3D bioprinted mesenchymal stromal cells in skin wound repair - Luo, Yuansen; Xu, Xuefeng; Ye, Zhiming; Xu, Qikun; Li, Jin; Liu, Ning; Du, Yongjun (Frontiers in Surgery, 2022)
Skin tissue regeneration and repair is a complex process involving multiple cell types, and current therapies are limited to promoting skin wound healing. Mesenchymal stromal cells (MSCs) have been proven to enhance skin tissue repair through their multidifferentiation and paracrine effects. However, there are still difficulties, such as the limited proliferative potential and the biological processes that need to be strengthened for MSCs in wound healing. Recently, three-dimensional (3D) bioprinting has been applied as a promising technology for tissue regeneration. 3D-bioprinted MSCs could maintain a better cell ability for proliferation and expression of biological factors to promote skin wound healing. It has been reported that 3D-bioprinted MSCs could enhance skin tissue repair through anti-inflammatory, cell proliferation and migration, angiogenesis, and extracellular matrix remodeling. In this review, we will discuss the progress on the effect of MSCs and 3D bioprinting on the treatment of skin tissue regeneration, as well as the perspective and limitations of current research.